The Best Strategy For Dealing With Business Conflicts: Strategic Choices In Drafting Clauses In Arbitration Agreements And The Application Of Expedited Procedures - Wiguna, Adhi Gani; Ansari, Teuku Syahrul; Astawa, I Ketut; Setiady, Tri (Universitas Wiralodra, 2024)
Arbitration or the root word in (Latin) ''arbitrare'' means